Analysis of Value Environment of Educational Establishment - Levkivska, Krystyna (Pedagogical Discourse, 2014)
The article presents the main branch approaches to the classification of values education .It was designed system of philosophical ideas about the values of their content and classification of the plane of pedagogical research. The characterization and analysis of the different approaches to the classification of values are presented here on: substantive and subjective, internal and external, dominant, divergent and deviant, the absolute (timeless) and situational, spiritual, moral, religious, aesthetic, physical, personal, group and universal. The article reveals the essence and the content of personal, group, and universal values, taking into account the specifics of innovative educational institutions; educational characteristics represented groups of values are given. Conclusions on the feasibility of the classification of values as an innovative educational institution of general and specific teaching (values, goals and values, resources) are formulated here. It is marked the peculiarity of the place and role in the educational process of the establishment of innovative basic values of the person and the institution as an educational institution.